2017
DOI: 10.1007/82_2017_32
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Non-coding RNAs in Respiratory Syncytial Virus (RSV) Infection

Abstract: Analysis of host gene expression profiles following viral infections of target cells/tissues can reveal crucial insights into the host: virus interaction and enables the development of novel therapeutics and prophylactics. Regions of the host genome that do not code for protein, encode structural, and functional non-coding RNAs that are important not only in regulation of host gene expression but also may impact viral replication. This review summarizes the role of host non-coding RNAs during replication of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 227 publications
0
4
0
Order By: Relevance
“…The world hardly learns to deal with a virus when new emerges and threatens the future of humanity. A similar situation arises when a new strain of coronavirus (CoV) not previously identified in humans was reported last year (2019) [1]. Positive-sense RNA viruses called corona viruses belong to the Coronaviridae family that are distributed broadly among human and mammals.…”
Section: Introductionmentioning
confidence: 75%
“…The world hardly learns to deal with a virus when new emerges and threatens the future of humanity. A similar situation arises when a new strain of coronavirus (CoV) not previously identified in humans was reported last year (2019) [1]. Positive-sense RNA viruses called corona viruses belong to the Coronaviridae family that are distributed broadly among human and mammals.…”
Section: Introductionmentioning
confidence: 75%
“…Viruses are dangerous pathogens and can cause irreversible losses to human lives and economy. The world hardly learns to deal with a virus when new emerges and threatens the future of humanity [ 1 ]. A similar situation arises when a new strain of coronavirus (CoV) not previously identified in humans was reported last year (2019).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that ncRNAs can affect different stages of the viral cycle and the host's immune responses. In return, viruses regulate ncRNA expression to facilitate their own replication cycle 55‐57 . Recently, it has been observed that some ncRNAs can target the genome or some genes of SARS‐CoV‐2 58–60 .…”
Section: Discussionmentioning
confidence: 99%